2023
DOI: 10.1186/s13071-023-05668-6
|View full text |Cite
|
Sign up to set email alerts
|

Using ecological niche modeling to predict the potential distribution of scrub typhus in Fujian Province, China

Abstract: Background Despite the increasing number of cases of scrub typhus and its expanding geographical distribution in China, its potential distribution in Fujian Province, which is endemic for the disease, has yet to be investigated. Methods A negative binomial regression model for panel data mainly comprising meteorological, socioeconomic and land cover variables was used to determine the risk factors for the occurrence of scrub typhus. Maximum entropy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
1
2
1
Order By: Relevance
“…Few studies have discussed the relationship between wind speed and scrub typhus. A study in Fujian by Li et al showed that wind speed was negatively correlated with scrub typhus, which was not consistent with the impact of wind speed in the south on scrub typhus in this study [ 52 ]. The reasons for these phenomena may be: firstly, the regional characteristics of different research areas may lead to changes in climate conditions, which had different impacts on the epidemiology of scrub typhus.…”
Section: Discussioncontrasting
confidence: 98%
“…Few studies have discussed the relationship between wind speed and scrub typhus. A study in Fujian by Li et al showed that wind speed was negatively correlated with scrub typhus, which was not consistent with the impact of wind speed in the south on scrub typhus in this study [ 52 ]. The reasons for these phenomena may be: firstly, the regional characteristics of different research areas may lead to changes in climate conditions, which had different impacts on the epidemiology of scrub typhus.…”
Section: Discussioncontrasting
confidence: 98%
“…On the other hand, there is a negative correlation between the incidence of scrub typhus and WIND and PRS. These findings align with the existing literature [ 1 , 10 , 16 , 17 ]. No statistical association was found between the incidence of the disease and weekly average precipitation.…”
Section: Discussionsupporting
confidence: 92%
“…Among the models commonly available, the MaxEnt model was more widely used, and it was often used to explore regional and environmental risk factors for the spread of naturally focused diseases. For example, MaxEnt model combined with geographic information systems (GIS) has been applied to predict the distribution of multiple types of infectious diseases, such as African swine fever, Japanese encephalitis, schistosomiasis and scrub typhus [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%